High-molecular-weight polysiloxane polyether type polyurethane urea and preparation method thereof

By adopting a semi-bulk-semi-solution synthesis method to synthesize high molecular weight polysiloxane polyether polyurethane urea, the deficiencies in mechanical properties, biological stability and processing convenience of polymer heart valve materials are solved, and high efficiency and environmental protection are achieved. Preparation of polymeric heart valve materials.

CN119331209AActive Publication Date: 2025-01-21FUWAI HOSPITAL CHINESE ACAD OF MEDICAL SCI & PEKING UNION MEDICAL COLLEGE
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411759658.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-01-16
Filing Date
2024-12-03
Publication Date
2025-01-21
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The existing polymer heart valve materials have shortcomings in terms of mechanical properties, biostability and processing convenience, and are difficult to meet the needs of high molecular weight, narrow dispersion, soft and hard segment separation, high crosslinking, excellent biocompatibility and low cost. Require.

Method used

The synthesis method of semi-body-semi-solution is used, and polysilica oxyxane and polyether are used as a hybrid soft segment, small molecular diol and dihanramine are used as chain expansion agents. It is 40%to 45%, without adding catalysts, it is directly used for immersion process.

Benefits of technology

It achieves high mechanical properties, excellent biocompatibility and biological stability of polymer heart valve materials, simplifies the processing process, reduces costs, and is suitable for the preparation of artificial heart valves.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331209A_ABST
    Figure CN119331209A_ABST
Patent Text Reader

Abstract

The invention relates to high-molecular-weight polysiloxane polyether type polyurethane urea and a preparation method thereof, and belongs to the field of development and application of biomedical materials. The high molecular weight polysiloxane polyether type polyurethane urea polymer is composed of a soft segment and a hard segment, and the content of the hard segment is 25 wt.%-45 wt.%; the soft segment comprises polydimethylsiloxane and polyether, and the hard segment comprises diisocyanate and a micromolecule chain extender. A bulk-solution combined polymerization method is adopted for preparation. The preparation method comprises the following steps: firstly, carrying out prepolymerization reaction on polyether glycol, polydimethylsiloxane and diisocyanate in a body form; adding a secondary chain extender after prepolymerization is completed, then adding a solvent to dissolve a reaction system into a solution, and adding a main chain extender to react until the reaction is completed. The method is simple and reliable, the prepared material is excellent in biocompatibility and biological stability and good in mechanical property, and the prepared polyurethane urea material is a polymer heart valve material with great application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high molecular weight polysiloxane polyether polyurethane urea and a preparation method thereof, and in particular to a preparation method of a high molecular weight polysiloxane polyether polyurethane urea applied to polymer heart valves and directly applicable to a dip coating process, and belongs to the field of biomedical material development and application. Background Art

[0002] Compared with biological valves, polymer valves are not only more durable, but also thinner and more resistant to bending, which will make them shine in the field of minimally invasive heart valves, expand the variety of heart valve surgery and greatly reduce the pain and postoperative recovery time of surgical patients. In addition, compared with mechanical valves, their excellent biocompatibility can eliminate the use of anticoagulants after surgery, greatly improving the quality of life of patients and reducing the risk of sequelae. At the same time, the relatively cheap material cost and processing cost make the price of polymer valves and surgical costs lower, reducing the economic burden for patients in underdeveloped countries and regions. With the development of materials and the advancement of technology, it is believed that in the near future, artificial heart valves will enter the polymer era.

[0003] Regarding the development of polymer valves that meet the requirements of use, the polymer should meet the following requirements: (1) have a high molecular weight and a narrow dispersion; (2) have soft segments and hard segments in the polymer structure, and have a certain degree of phase separation; (3) have sufficient (physical or chemical) cross-links between the polymer segments to increase rebound and avoid excessive creep effects; (4) have good biological stability; (5) have low nonspecific protein adhesion; (6) have excellent blood compatibility; (7) have simple processing methods, such as solution processing (casting, dip coating, electrospinning), melt processing, 3D printing, etc.; (8) be cheap and low cost.

[0004] In order to develop a new type of durable polymer heart valve, researchers at home and abroad are working hard to find the perfect polymer material and processing method for artificial heart valves. Researchers at the University of Cambridge used polystyrene-ethylene-butylene polystyrene copolymer (SEBS) and injection molding to prepare an artificial heart valve with a leaflet thickness of 0.4 mm, which has excellent biocompatibility and has the highest fatigue number reported so far - 1.2 billion times (Joanna R. Stasiak et al., Biomater. Sci., 2020, 8, 4467). They first used SEBS29 (PS content of 29%) to prepare a stent. The stent was then placed in the mold, and the molten SEBS20 (PS content of 20%) was injected into the mold (each leaflet) from the small hole in the middle of the leaflet and overmolded on the previously made stent. The area above the injection point mainly shows the circumferential direction of the cylinder, similar to the direction of collagen fibers in natural heart valve tissue. Below the injection point, a bimodal orientation is formed, with part of the material arranged along the flow direction and part perpendicular to the flow direction. This is most similar to the fiber structure of natural biological valves. After the injection is completed, the mold is slowly cooled down (annealed) for 10 minutes. Annealing helps the orientation of polymer molecules and enhances the orderliness of its cylindrical configuration. TaurusApex, developed by Peijia Medical, a domestic high-tech heart valve company, is the first domestic polymer interventional valve in my country to publish laboratory and animal experimental data. The artificial heart valve adopts a multi-layer bionic composite structure - it has anisotropy characteristics similar to that of the native valve, and can also meet the requirements of biocompatibility, physical properties and fatigue performance.

[0005] Whether it is SEBS or multilayer biomimetic composite structural materials, their processing and synthesis methods are relatively cumbersome, and the biocompatibility and mechanical properties of SEBS have yet to be investigated. These points are particularly important for polymer heart valves. The recently developed siloxane polyurethane and siloxane polyurethane urea are a class of materials that have both biocompatibility and mechanical properties, and the addition of polysiloxane greatly improves its biostability, making it a class of artificial heart valve materials with great development prospects. Biostable poly 1,6-hexanediol-polydimethylsiloxane polyurethane (urea) is such a synthetic polymer material that has both excellent mechanical properties and biocompatibility (PA Gunatillake et al., PolymRev, 2019, 59(3): 391-417; LS Dandeniyage et al., J Biomed Mater Res Part B, 2018:106B: 1712–1720). Foldax has developed artificial heart valves using this material and conducted clinical experimental research. In addition, South Africa's SAT and DSM have cooperated to use DSM's Carbosil 2080A TSiPCU polymer interventional valve, which has completed animal experiments and is about to enter the clinical experimental research stage. Both of the above polymer valves use silicone-modified polyurethane and polyurethane urea materials, showing excellent biostability, mechanical properties and biocompatibility, and both use a dip-coating solution processing method. This processing method greatly retains the original properties of the material, and the processing method is simple and convenient.

[0006] Biostable polyurethane was developed under the demand of long-term implantable medical devices such as catheters and cardiac pacemaker wires. The development of biostable polyurethane has gone through the following stages: In 1967, the application of polyurethane in biomedical materials was first reported, but the ester bonds in the soft segment of polyester polyurethane are easily degraded by water molecules, and are generally not used as biostable polyurethane. The subsequent development of polyether polyurethane opened up the application of biostable polyurethane, but the ether bonds on the polyether chain segment are easily oxidized and degraded, which limits its further application. In order to improve its biostability, the scientific community has proposed two methods: one is to completely replace polyether with polycarbonate with better biostability. Although the biostability of both polycarbonate polyurethane and polysiloxane polyether polyurethane has been improved, polycarbonate polyurethane still has degradation; the other is to partially replace polyether with polysiloxane. The development of polysiloxane polyether polyurethane can be divided into three stages: polysiloxane polyurethane, but because polysiloxane is a non-polar macromolecule, its compatibility with carbamate and urea groups is poor, resulting in poor mechanical properties. This led to the synthesis and development of polysiloxane-polyether co-soft segment polyurethane, and the formation of two commercial products - Elast-Eon and PurSil. In subsequent studies, it was found that both polyurethane materials have excellent biocompatibility and biostability, meeting the requirements for long-term implant materials. However, as an artificial heart valve, the mechanical properties cannot meet the requirements, so the researchers adjusted the mechanical properties and enhanced the biostability by molecular regulation and modification of polyurethane. PA Gunatillake et al. prepared PHMO-PMDS polyurethane urea based on Elast-Eon 2A by using a mixed chain extender composed of 1,3-dihydroxybutyl-1,1,3,3-tetramethyldisilane (BHTD) and ethylenediamine (EDA) in a molar ratio of 1:1 instead of a single chain extender BDO (PAGunatillake et al., US2017119923A1). The introduction of urea groups increases the number of hydrogen bonds between molecular chains and also improves the microphase separation structure. Compared with Elast-Eon 2A and other polyurethane materials, its elasticity, tensile strength and tear strength are significantly improved. More importantly, no yielding phenomenon occurs on the stress-strain curve, indicating that the PHMO-PMDS polyurethane urea has good creep resistance (LS Dandeniyage et al., J Biomed Mater Res Part B, 2018, 106: 1712–1720). In addition, the development timeline of artificial heart valves is similar to that of biostable polyurethanes. This also shows that the development and application of new materials can promote the updating and iteration of the industry.However, the research on biostable polyurethane in China has just started, and the new generation of polymer artificial valves based on biostable polyurethane will be the future development direction worldwide. In this case, it is urgent to carry out research on polysiloxane polyurethane.

[0007] For polymer artificial heart valves, the choice of processing method is crucial. Currently, there are two processing methods: solution processing and melt processing. Melt processing requires large instruments and more process exploration. Moreover, for polyurethane and polyurethane urea, the melt processing method will destroy the original molecular structure, causing molecular chain breakage, etc., which will in turn affect the mechanical properties and biocompatibility. The solution processing method has low temperature, is easy to control, simple to operate, and will not damage the molecular structure of polyurethane urea. It is an advanced molding method for preparing polyurethane artificial heart valves.

[0008] Therefore, based on the above practical needs, the present invention develops a high molecular weight polysiloxane polyether polyurethane urea directly applied to the dip coating process to meet the requirements of polymer artificial heart valves for mechanical properties, biostability, biocompatibility and processing convenience. Summary of the invention

[0009] In order to meet the requirements of polymer artificial heart valves for the molecular weight, biocompatibility, mechanical properties, biological stability and processing performance of polyurethane urea materials, the present invention provides a high molecular weight polysiloxane polyether type polyurethane urea that can be directly applied to the dip coating process and a preparation method thereof, wherein a semi-bulk-semi-solution synthesis method is adopted, polysiloxane and polyether are used as mixed soft segments, and small molecule diols and small molecule diamines are used as chain extenders to synthesize high molecular weight polysiloxane polyether type polyurethane (urea) with excellent biological stability and good mechanical properties. The polyurethane urea material synthesized by the method can be used for dip coating to prepare artificial heart valves without adding catalysts or subsequent treatment, which is convenient, fast and environmentally friendly.

[0010] The present invention partially replaces polyether diol with polydimethylsiloxane (PDMS) in a specific ratio, and uses polyether diol and polydimethylsiloxane (PDMS) as mixed soft segments, uses small molecule diol and diamine as mixed chain extenders and together with diisocyanate as hard segments, and uses a semi-bulk-semi-solution synthesis method to prepare a high molecular weight polysiloxane polyether polyurethane urea with a hard segment content of 40% to 45% for polymer heart valves, which can be directly applied to the dip coating process. The material contains about 35% of polysiloxane components, and the surface energy of polysiloxane is low. During the solution processing, it can migrate to the surface and gradually enrich into a polysiloxane layer to protect the material from biodegradation, thereby achieving the purpose of improving biological stability. The use of dual chain extenders and dual soft segments increases the number of phases to balance the degree of microphase separation and improve mechanical and biological stability. Using small molecule diamine as the main chain extender, urea groups that can generate double hydrogen bonds are introduced, increasing the number of hydrogen bonds in polyurethane urea to improve the biostability, tensile strength, tear strength and creep resistance of polymer materials. At the same time, the semi-bulk-semi-solution polymerization method not only increases the reaction rate, but also reduces the use of catalysts during the reaction, making the reaction system more environmentally friendly and avoiding the introduction of heavy metal ions. The polyurethane urea material generated by the reaction has the advantage of high molecular weight, which greatly improves the mechanical properties of the polyurethane urea material. In addition, the synthesized polyurethane urea solution can be used for dip coating to prepare polymer valves without subsequent treatment, which is convenient and quick.

[0011] In order to achieve the above object, the present invention adopts the following technical solution: The invention provides a polysiloxane polyether polyurethane urea, which consists of a hard segment and a soft segment; the hard segment has a content of 40wt.% to 45wt.%, and comprises a diisocyanate and a small molecule chain extender; the soft segment comprises polydimethylsiloxane and polyether, and the proportion of the polydimethylsiloxane in the soft segment is 55-65%, preferably 60%.

[0012] The polysiloxane polyether polyurethane urea is a random copolymer with a number average molecular weight of 140,000-160,000, a weight average molecular weight of 250,000-300,000, and a molecular weight distribution index of ≤1.9.

[0013] The polyether is polytetrahydrofuran with a number average molecular weight of 500-3000; the polydimethylsiloxane is α,ω-bis(hydroxyethoxypropyl)polydimethylsiloxane with a number average molecular weight of 500-3000; the diisocyanate is diphenylmethane diisocyanate. The mass ratio of the diisocyanate to the hard segment is 70wt.%-75wt.%.

[0014] The small molecule chain extender includes a secondary chain extender and a primary chain extender, wherein the secondary chain extender is a C1-C6 diol, preferably butanediol, and the primary chain extender is a C1-C6 diamine, preferably ethylenediamine. Preferably, the weight ratio of butanediol to ethylenediamine is 3:2.

[0015] The invention discloses a method for preparing a high molecular weight polysiloxane polyether type polyurethane urea which can be directly applied to a dip coating process, and adopts a bulk-solution combined polymerization method for preparation; firstly, at a relatively high temperature, polyether diol (polyether diol), polydimethylsiloxane and diisocyanate are used to carry out a prepolymerization reaction in the form of a bulk; after the prepolymerization is completed, a secondary chain extender is added, and then the reaction is continued for a period of time at a set temperature, and then a proper amount of solvent is added to dissolve the reaction system into a solution, and a primary chain extender is added in a solution state and reacted for a period of time at a suitable temperature until the reaction is completed; the polysiloxane polyether type polyurethane urea solution after the complete reaction can be directly cast into a film to prepare a polymer membrane, and a polyurethane urea solid material can be obtained after solution replacement and drying, or the solution viscosity can be adjusted by a simple operation of adding a solution or evaporating the solution to carry out dip coating processing into a polymer heart valve.

[0016] Different ways of hydrogen bonding between urethane groups and urea groups in the hard segment:

[0017] The present invention further provides a method for preparing a high molecular weight polysiloxane polyether polyurethane urea which can be directly applied to a dip coating process, comprising the following steps: (1) polymerizing a polyether diol and a diisocyanate, wherein the molar ratio of the polyether diol to the diisocyanate is 2:1; (2) After the reaction in step (1) is completed, polydimethylsiloxane and diisocyanate are added into the system and heated for polymerization; (3) After the reaction in step (2) is completed, a secondary chain extender is added into the system for chain extension; (4) After the reaction in step (3) is completed, a main chain extender is added into the system for chain extension.

[0018] The more specific steps are as follows: (1) Add polyether diol to a reaction vessel, heat it, and add 1 / 2 equimolar amount of diisocyanate after the polyether diol is completely dissolved; after the sample is fully dissolved and miscible under mechanical stirring, keep the temperature at the reaction temperature, and introduce dry nitrogen to maintain the nitrogen atmosphere, with a ventilation rate of 1-2 bubbles per second. The reaction process is detected by infrared until the sample reaches 2270cm -1 The end point of the reaction is when the characteristic absorption peak of isocyanate disappears. (2) maintaining the temperature of the reaction system in step (1) at 55-65° C., and adding polydimethylsiloxane (PDMS) and an appropriate amount of diisocyanate, wherein the mass ratio of polyether diol to PDMS is 2:8 to 6:4, and after the newly added materials are melted and mixed evenly, maintaining the temperature at the reaction temperature, continuing to maintain the nitrogen ventilation rate of 1-2 bubbles per second, and reacting under strong stirring; (3) After the prepolymerization reaction is completed, the temperature is maintained at 55-65° C., an appropriate amount of secondary chain extender is added, and after it is fully dissolved and stirred evenly, the temperature is adjusted to a preset temperature, and nitrogen is continuously introduced to carry out the reaction; (4) adding a solvent to a preset concentration to the reaction system after the reaction in step (3) is completed, and transferring the reaction system to a pre-set low-temperature bath after sufficient dissolution. When the temperature is constant, adding a solution containing a main chain extender to the reaction system by dropwise addition; maintaining the temperature constant and continuously introducing nitrogen to carry out the reaction; then, transferring the reaction system to an oil bath at a preset temperature to continue the reaction to obtain a polyurethane urea solution (polysiloxane polyether type polyurethane urea solution).

[0019] In step (1), the polyether glycol (polyether diol) includes but is not limited to polytetramethylene oxide glycol (PTMG), polypropylene glycol (PPG), polyhexamethylene oxide glycol, polyethylene glycol (PEG), etc., and has a molecular weight range of 500 to 3,000.

[0020] Diisocyanates include, but are not limited to, diphenylmethane diisocyanate (MDI), 4,4'-dicyclohexylmethane diisocyanate (HMDI), hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), xylene diisocyanate and / or isophorone diisocyanate (IPDI), etc.

[0021] The temperature for heating and dissolving the polyether diol is 55-65°C.

[0022] The reaction temperature ranges from 60°C to 100°C, and the preferred temperature range is 70°C to 80°C.

[0023] In step (2), the polydimethylsiloxane (PDMS) includes but is not limited to α,ω-bis(hydroxyethoxypropyl) polydimethylsiloxane, bis(hydroxybutyl) polydimethylsiloxane, bis(hydroxypropyl) polydimethylsiloxane and / or bis(aminopropyl) polydimethylsiloxane, etc., and has a molecular weight range of 500~4,000, and a preferred molecular weight range of 500~3,000.

[0024] In step (2), the appropriate amount of diisocyanate means that the overall R value is 0.98-1.05, preferably 0.99-1.02. The R value is the molar ratio of the isocyanate group to the sum of the hydroxyl group and the amino group.

[0025] The reaction temperature ranges from 60°C to 100°C, preferably from 70°C to 80°C; the reaction time ranges from 0 to 8h, preferably from 0.5 to 8h.

[0026] In step (3), the secondary chain extender includes but is not limited to hydroquinone-di(β-hydroxyethyl) ether, N-dihydroxy(diisopropyl)aniline, 1,4-butanediol, 1,6-hexanediol, 1,3-propylene glycol, 1,5-pentanediol, 1,4-di(2-hydroxyethoxy)benzene and / or N-methyldiethanolamine, etc.; the added amount ranges from 0 to 100% of the total content of the chain extender, and the molar ratio of the secondary chain extender to the polyether diol ranges from 0 to 5.

[0027] The preset temperature range is 25°C-100°C, preferably 50°C-100°C; the reaction time range is 0-8h, preferably 0.5-5h.

[0028] In step (4), the solvent includes but is not limited to DMAc (N,N-dimethylacetamide), DMSO (dimethyl sulfoxide), DMF (N,N-dimethylformamide), THF (tetrahydrofuran), DCE (dichloroethane), dioxane, toluene and / or xylene.

[0029] The concentration of the synthesized polymer is preset to be in the range of 10 wt.%-30 wt.%.

[0030] The main chain extender includes but is not limited to diethylaminoethanol, 1,2-ethylenediamine (EDA), 1,4-butanediamine, 3,3'-dichloro-4,4'-diaminodiphenylmethane and / or 1,6-hexanediamine, etc.; the addition amount ranges from 0 to 100% of the total content of the chain extender, and the molar ratio of the main chain extender to the polyether diol ranges from 0 to 5; the main chain extender is dissolved in the same solvent as that added to the reaction system.

[0031] The temperature range of the low temperature bath is 0°C-50°C; the reaction time range is 0-8h, preferably 0.5-8h.

[0032] The preset temperature range of the oil bath pot is 25°C-100°C, preferably 50°C-100°C; the reaction time range is 0-8h, preferably 0.5-8h. The total reaction time range of adding the main chain extender is 0-12h.

[0033] The method of the present invention may also include step (5), wherein the fully reacted polymer solution is subjected to adding or evaporating a solvent, or without subsequent operation, to obtain a polyurethane urea solution of a certain concentration, and then the polyurethane urea solution is dried by a simple dipping process to obtain a polymer valve; or the fully reacted polysiloxane polyether polyurethane urea solution is directly subjected to film casting to prepare a polymer membrane or subjected to solution replacement and drying to obtain a polyurethane urea solid material.

[0034] In step (5), the concentration of the polyurethane urea solution is in the range of 5wt.%-30wt.%, preferably 10wt.%-30wt.%; the dipping process belongs to the solution processing range; the drying temperature range is 25°C-80°C. The solution viscosity is adjusted by a simple operation of adding solution or evaporating the solution for dipping and processing into a polymer heart valve, and the adjusted solution concentration is 5wt.%-30wt.%.

[0035] In the method of the present invention, in terms of parts by mass, in step (1), 2000-6000 parts of polyether diol and 500-600 parts of diisocyanate are added; in step (2), 4000-8000 parts of polydimethylsiloxane (PDMS) and 2500-5800 parts of diisocyanate are added; in step (3), 540-1846 parts of secondary chain extender are added; and in step (4), 360-756 parts of primary chain extender are added.

[0036] In the method of the present invention, the prepolymerization reaction is carried out in bulk, and no catalyst is added to the entire reaction system.

[0037] The ratios or “parts” of different substances mentioned in the present invention are by mass ratios unless otherwise specified.

[0038] The benefits of the present invention are: (1) By adjusting the content of the hard segment and the ratio of polyether to polydimethylsiloxane, and controlling the molecular weight and molecular weight distribution, the mechanical properties are regulated to obtain a material with a higher ultimate tensile strength and tear strength and a controlled Young's modulus E; (2) The semi-bulk-semi-solution processing method not only improves the reaction rate and shortens the reaction time, but also allows direct dip coating, which is green and environmentally friendly; no catalyst is used, ensuring biological safety; (3) The chain extension method of double chain extenders was adopted to improve the reaction activity, and the urea group was introduced to increase the number of hydrogen bonds and improve mechanical properties such as tensile strength and tear resistance.

[0039] The present invention also provides an artificial heart valve, the material of which is the polysiloxane polyether polyurethane urea described in the present invention.

[0040] The invention is advanced and practical, and the material can meet the requirements for long-term implantation of polymer heart valves.

[0041] The high molecular weight polysiloxane polyether polyurethane urea prepared by the present invention and directly applicable to the dip coating process adopts polyether diol and polydimethylsiloxane diol as soft segments and aromatic diisocyanate and small molecule diol / diamine as hard segments. The synthesis process is to prepare the polysiloxane polyether polyurethane urea solution by a semi-bulk and semi-solution polymerization method without a catalyst.

[0042] The polyurethane urea solution can be cast into a film or dip-coated to obtain a polyurethane urea film material. The content of polydimethylsiloxane in the obtained polyurethane urea material accounts for about 35wt% of the whole, and because the surface energy of polydimethylsiloxane is low, it will spontaneously migrate and enrich to the surface of the material during the solution processing, forming a polydimethylsiloxane protective layer to protect or reduce the impact of hydrolysis, enzymolysis and oxidative degradation of the material. In addition, the polyether component and small molecule chain extender in the polyurethane urea material can play the role of a compatibilizer of non-polar polydimethylsiloxane and polar carbamate and urea groups through intermolecular hydrogen bonds to improve the phase separation degree of the material and improve the overall mechanical strength and biological stability.

[0043] The polysiloxane polyether polyurethane urea solution prepared by the present invention can be directly used for dipping and casting without complicated processes such as post-treatment. At the same time, the solution concentration can be adjusted by simply adding solvents at a later stage to meet the needs of different solution processing methods. The number average molecular weight of the polysiloxane polyether polyurethane urea prepared by the present invention is 140,000-160,000, the weight average molecular weight is 250,000-300,000, and the molecular weight distribution is ≤1.9, which can meet the use requirements of polymer heart valves for material molecular weight. It can be seen from the tensile performance test results that the tensile strength of this series of polyurethane urea materials exceeds 40MPa, which is far higher than the test results of currently existing biological valves, and the tear strength meets the requirements of polymer heart valves. What is particularly important is that the polyurethane urea material exhibits excellent biocompatibility and biostability.

[0044] In summary, the method for preparing the polymer heart valve material-polysiloxane polyether polyurethane of the present invention is simple and reliable, and the prepared material has excellent biocompatibility, biostability and mechanical properties. The polyurethane urea material is a polymer heart valve material with great application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 is the infrared spectra of polysiloxane polyether polyurethane urea with different hard segment contents prepared by the present invention; Figure 2 is a gel permeation chromatogram of polysiloxane polyether polyurethane urea with different hard segment contents prepared by the present invention in DMF; Figure 3 middle, Figure 3(a) is a stress-strain curve of polysiloxane polyether polyurethane urea with different hard segment contents prepared by the present invention under dry conditions; Figure 3 (b) is the stress-strain curve under wetting conditions; Figure 3 (c) is the tensile modulus of polysiloxane polyether polyurethane urea with different hard segment contents under dry and wet conditions; Figure 4 The present invention is a biocompatibility test (four coagulation items, cytotoxicity) at a hard segment content of 40wt.%; Figure 5 This is a biological stability test (in vivo and in vitro) of the present invention at a hard segment content of 40 wt.%. DETAILED DESCRIPTION

[0046] The present invention discloses a method for preparing a high molecular weight polysiloxane polyether polyurethane urea which can be directly applied to a dip coating process, comprising the following steps: (1) Add 40 parts by weight of polyether diol (e.g., PTMG) to a reaction vessel, raise the temperature to 60°C, and add 1 / 2 mole of diisocyanate (e.g., MDI) after the polyether diol is completely dissolved. After the sample is fully dissolved and miscible under mechanical stirring, raise the reaction temperature to a preset temperature, and introduce dry nitrogen to maintain a nitrogen atmosphere at a flow rate of 1-2 bubbles per second. The reaction process is detected by infrared until the sample is fully dissolved at 2270cm -1 The reaction endpoint is when the characteristic absorption peak of isocyanate disappears; polyether diols include but are not limited to PEG, PTMG, PTMO, PHMO, PPG, etc.; isocyanates include but are not limited to diphenylmethane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, and xylene diisocyanate; the predetermined temperature range is 25°C-100°C.

[0047] (2) The temperature of the reaction system in step (1) is lowered to 60°C, and 60 parts by weight of polydimethylsiloxane (PDMS) and an appropriate amount of diisocyanate are added thereto. After the newly added materials are melted and mixed evenly, the temperature is raised to an appropriate temperature, and the nitrogen ventilation rate is maintained at 1-2 bubbles per second. The reaction is carried out for a period of time under strong stirring; polydimethylsiloxane (PDMS) includes but is not limited to α, ω-bis (hydroxyethoxypropyl) polydimethylsiloxane, bis (hydroxybutyl) polydimethylsiloxane, bis (hydroxypropyl) polydimethylsiloxane, bis (aminopropyl) polydimethylsiloxane, etc., with a molecular weight range of 500-4,000; the appropriate temperature range is 25°C-100°C; the reaction time range is 0-8h.

[0048] (3) After the prepolymerization reaction is completed, the temperature is lowered to 60°C, and an appropriate amount of secondary chain extender is added. After it is fully dissolved and stirred evenly, the temperature is adjusted to the preset temperature, and nitrogen is continuously introduced to react for a period of time; the secondary chain extender includes but is not limited to hydroquinone-di(β-hydroxyethyl) ether, N-dihydroxy(diisopropyl)aniline, 1,4-butanediol, 1,6-hexanediol, 1,3-propylene glycol, 1,5-pentanediol, etc.; the preset temperature range is 25°C-100°C; the reaction time range is 0-8h.

[0049] (4) Add solvent to the reaction system after the reaction in step (3) to a preset concentration, transfer the reaction system to a pre-set low-temperature bath after sufficient dissolution, and add a solution containing an appropriate amount of main chain extender to the reaction system by dropwise addition when the temperature is constant. Maintain the temperature and continue to introduce nitrogen for a period of time; the temperature range of the low-temperature bath is 0°C-50°C; the main chain extender includes but is not limited to diethylaminoethanol, 1,2-ethylenediamine (EDA), 1,4-butanediamine, 3,3'-dichloro-4,4'-diaminodiphenylmethane, 1,6-hexanediamine, etc.; the solvent includes but is not limited to DMAc, DMSO, DMF, THF, DCE, dioxane, toluene, xylene, etc.; the reaction time range is 0-8h; the preset concentration range is 10%-30%.

[0050] (5) After the addition of the main chain extender is completed and the reaction is continued in the low temperature bath for a period of time, the reaction system is transferred to an oil bath pot at a preset temperature and the reaction is continued for a period of time; the temperature range is 25°C-100°C; the reaction time range is 0-8h.

[0051] (6) After the reaction is completed, the fully reacted polymer solution can be added / evaporated with a solvent or without subsequent operation to obtain a polyurethane urea solution with a fixed concentration, and the polyurethane urea solution can be used to obtain a polymer valve by a simple dip coating process and drying. The fixed concentration range is 10%-30%; the dip coating process belongs to the solution processing range; the drying temperature range is 25℃-80℃.

[0052] The present invention is further described below in conjunction with the accompanying drawings, tables and specific embodiments.

[0053] In the examples, unless otherwise specified, all feed ratios are in parts by mass.

[0054] Example 1 (Si28) Take 4000 parts of polytetrahydrofuran (M n=1000) was placed in a reaction vessel and heated to 60°C. After the polytetrahydrofuran was completely melted, 500 parts of MDI (diphenylmethane diisocyanate) was added thereto and dissolved in PTMG (polytetrahydrofuran). The temperature was raised to 80°C and dry nitrogen was introduced and maintained at a nitrogen atmosphere. The ventilation rate was maintained at 1-2 bubbles per second. The reaction process was detected by infrared until the temperature at 2270cm -1 The end point of the reaction is when the characteristic absorption peak of isocyanate disappears. The temperature of the reaction system is lowered to 60°C, and 6000 parts of α,ω-bis(hydroxyethoxypropyl)polydimethylsiloxane (Mn=1000) and 2500 parts of MDI are added thereto. After the newly added materials are melted and mixed evenly, the temperature is raised to 80°C, and the nitrogen ventilation rate is maintained at 1-2 bubbles per second. The reaction is stirred vigorously for 3 hours. After the prepolymerization reaction is completed, the temperature is lowered to 60°C, 540 parts of 1,4-butanediol are added, and after it is fully dissolved and stirred evenly, the temperature is adjusted to 80°C, and nitrogen is continuously introduced for 3 hours. Then, N,N-dimethylacetamide (DMAc) is added to the reaction system after the reaction is completed to a concentration of 25wt%. After it is fully dissolved, the reaction system is transferred to a pre-set low-temperature bath at 0°C. When the temperature is constant, a solution containing 360 parts of ethylenediamine (3mlDMAc) is added to the reaction system by dropwise addition. The temperature was kept constant and nitrogen was continuously introduced for 1 hour. The reaction system was then transferred to an oil bath at 80°C and the reaction was continued for 4 hours. The reaction was completed. The viscosity of the fully reacted polymer solution was 2542 mpa / s.

[0055] The hard segment content of the material is 28wt.%; the mass ratio of polydimethylsiloxane to the soft segment is 60wt.%; the mass ratio of diisocyanate to the hard segment is 73.5wt.%. The Fourier infrared spectrum is as follows Figure 1 As shown in Si28, the GPC elution curve is as follows Figure 2 The infrared spectrum can intuitively show that the polymer material is a polysiloxane polyether polyurethane urea polymer.

[0056] Example 2 (Si32) 4000 parts of polytetrahydrofuran (Mn=1000) were placed in a reaction vessel and heated to 60°C. After the polytetrahydrofuran was completely melted, 500 parts of MDI were added thereto and dissolved in PTMG. The temperature was raised to 80°C and dry nitrogen was introduced to maintain a nitrogen atmosphere with a ventilation rate of 1-2 bubbles per second. The reaction process was detected by infrared until the temperature at 2270cm -1The end point of the reaction is when the characteristic absorption peak of isocyanate disappears. The temperature of the reaction system is lowered to 60°C, and 6000 parts of α,ω-bis(hydroxyethoxypropyl)polydimethylsiloxane (Mn=1000) and 3120 parts of MDI are added thereto. After the newly added materials are melted and mixed evenly, the temperature is raised to 80°C, and the nitrogen ventilation rate is maintained at 1-2 bubbles per second. The reaction is stirred vigorously for 3 hours. After the prepolymerization reaction is completed, the temperature is lowered to 60°C, 650 parts of 1,4-butanediol are added, and after it is fully dissolved and stirred evenly, the temperature is adjusted to 80°C, and nitrogen is continuously introduced for 3 hours. Then, DMAc is added to the reaction system after the reaction is completed to a concentration of 25wt%. After it is fully dissolved, the reaction system is transferred to a pre-set low-temperature bath at 0°C. When the temperature is constant, a solution (3mlDMAc) containing 435 parts of ethylenediamine is added to the reaction system by dropwise addition. The temperature was kept constant and nitrogen was continuously introduced for 1 hour. The reaction system was then transferred to an oil bath at 80°C and the reaction was continued for 4 hours. The reaction was completed. The viscosity of the fully reacted polymer solution was 2800 mpa / s.

[0057] The hard segment content of the material is 32wt.%; the mass ratio of polydimethylsiloxane to the soft segment is 60wt.%; the mass ratio of diisocyanate to the hard segment is 74.2wt.%. The Fourier infrared spectrum is as follows Figure 1 As shown in Si32, the GPC elution curve is as follows Figure 2 As shown in Si32.

[0058] Example 3 (Si36) 4000 parts of polytetrahydrofuran (Mn=1000) were placed in a reaction vessel and heated to 60°C. After the polytetrahydrofuran was completely melted, 500 parts of MDI were added thereto and dissolved in PTMG. The temperature was raised to 80°C and dry nitrogen was introduced to maintain a nitrogen atmosphere with a ventilation rate of 1-2 bubbles per second. The reaction process was detected by infrared until the temperature at 2270cm -1The end point of the reaction is when the characteristic absorption peak of isocyanate disappears. The temperature of the reaction system is lowered to 60°C, and 6000 parts of α,ω-bis(hydroxyethoxypropyl)polydimethylsiloxane (Mn=1000) and 3827 parts of MDI are added thereto. After the newly added materials are melted and mixed evenly, the temperature is raised to 80°C, and the nitrogen ventilation rate is maintained at 1-2 bubbles per second. The reaction is stirred vigorously for 3 hours. After the prepolymerization reaction is completed, the temperature is lowered to 60°C, 780 parts of 1,4-butanediol are added, and after it is fully dissolved and stirred evenly, the temperature is adjusted to 80°C, and nitrogen is continuously introduced for 3 hours. Then, DMAc is added to the reaction system after the reaction is completed to a concentration of 25wt%. After it is fully dissolved, the reaction system is transferred to a pre-set low-temperature bath at 0°C. When the temperature is constant, a solution (3mlDMAc) containing 520 parts of ethylenediamine is added to the reaction system by dropwise addition. The temperature was kept constant and nitrogen was continuously introduced for 1 hour. The reaction system was then transferred to an oil bath at 80°C and the reaction was continued for 4 hours. The reaction was completed. The viscosity of the fully reacted polymer solution was 3410 mpa / s.

[0059] The hard segment content of the material is 36wt.%; the mass ratio of polydimethylsiloxane to the soft segment is 60wt.%; the mass ratio of diisocyanate to the hard segment is 74.6wt.%. The Fourier infrared spectrum is as follows Figure 1 As shown in Si36, the GPC elution curve is as follows Figure 2 As shown in Si36.

[0060] Example 4 (Si40) 4000 parts of polytetrahydrofuran (Mn=1000) were placed in a reaction vessel and heated to 60°C. After the polytetrahydrofuran was completely melted, 500 parts of MDI were added thereto and dissolved in PTMG. The temperature was raised to 80°C and dry nitrogen was introduced to maintain a nitrogen atmosphere with a ventilation rate of 1-2 bubbles per second. The reaction process was detected by infrared until the temperature at 2270cm -1The end point of the reaction is when the characteristic absorption peak of isocyanate disappears. The temperature of the reaction system is lowered to 60°C, and 6000 parts of α,ω-bis(hydroxyethoxypropyl)polydimethylsiloxane (Mn=1000) and 4627 parts of MDI are added thereto. After the newly added materials are melted and mixed evenly, the temperature is raised to 80°C, and the nitrogen ventilation rate is maintained at 1-2 bubbles per second. The reaction is stirred vigorously for 3 hours. After the prepolymerization reaction is completed, the temperature is lowered to 60°C, 923 parts of 1,4-butanediol are added, and after it is fully dissolved and stirred evenly, the temperature is adjusted to 80°C, and nitrogen is continuously introduced for 3 hours. Then, DMAc is added to the reaction system after the reaction is completed to a concentration of 25wt%. After it is fully dissolved, the reaction system is transferred to a pre-set low-temperature bath at 0°C. When the temperature is constant, a solution (3mlDMAc) containing 616 parts of ethylenediamine is added to the reaction system by dropwise addition. The temperature was kept constant and nitrogen was continuously introduced for 1 hour. The reaction system was then transferred to an oil bath at 80°C and the reaction was continued for 4 hours. The reaction was completed. The viscosity of the fully reacted polymer solution was 3387 mpa / s.

[0061] The hard segment content of the material is 40wt.%; the mass ratio of polydimethylsiloxane to the soft segment is 60wt.%; the mass ratio of diisocyanate to the hard segment is 75.0wt.%. The Fourier infrared spectrum is as follows Figure 1 As shown in Si40, the GPC elution curve is as follows Figure 2 As shown in Si40.

[0062] Example 5 (Si45) 4000 parts of polytetrahydrofuran (Mn=1000) were placed in a reaction vessel and heated to 60°C. After the polytetrahydrofuran was completely melted, 500 parts of MDI were added thereto and dissolved in PTMG. The temperature was raised to 80°C and dry nitrogen was introduced to maintain a nitrogen atmosphere with a ventilation rate of 1-2 bubbles per second. The reaction process was detected by infrared until the temperature at 2270cm -1The end point of the reaction is when the characteristic absorption peak of isocyanate disappears. The temperature of the reaction system is lowered to 60°C, and 6000 parts of α,ω-bis(hydroxyethoxypropyl)polydimethylsiloxane (Mn=1000) and 5800 parts of MDI are added thereto. After the newly added materials are melted and mixed evenly, the temperature is raised to 80°C, and the nitrogen ventilation rate is maintained at 1-2 bubbles per second. The reaction is stirred vigorously for 3 hours. After the prepolymerization reaction is completed, the temperature is lowered to 60°C, 1134 parts of 1,4-butanediol are added, and after it is fully dissolved and stirred evenly, the temperature is adjusted to 80°C, and nitrogen is continuously introduced for 3 hours. Then, DMAc is added to the reaction system after the reaction is completed to a concentration of 25wt%. After it is fully dissolved, the reaction system is transferred to a pre-set low-temperature bath at 0°C. When the temperature is constant, a solution (3mlDMAc) containing 756 parts of ethylenediamine is added to the reaction system by dropwise addition. The temperature was kept constant and nitrogen was continuously introduced for 1 hour. The reaction system was then transferred to an oil bath at 80°C and the reaction was continued for 4 hours. The reaction was completed. The viscosity of the fully reacted polymer solution was 3649 mpa / s.

[0063] The hard segment content of the material is 45wt.%; the mass ratio of polydimethylsiloxane to the soft segment is 60wt.%; the mass ratio of diisocyanate to the hard segment is 75.0wt.%. The Fourier infrared spectrum is as follows Figure 1 As shown in Si45, the GPC elution curve is as follows Figure 2 As shown in Si45.

[0064] Taking five samples (labeled Si28, Si32, Si36, Si40, Si45) with hard segment contents of 28wt%, 32wt%, 36wt%, 40wt% and 45wt% respectively prepared in Examples 1-5 as examples, the structure and performance characterization process of high molecular weight polysiloxane polyether polyurethane urea prepared by the scheme and steps of the present invention and directly applicable to the dip coating process is explained.

[0065] 1) From the viscosity of the obtained polymer solution, when the solution concentration is 25%, the viscosity is 2500mpa / s-3000mpa / s, the solution is transparent without stratification, precipitation, suspension, and solid precipitation. After adding solvent, the viscosity of the polyurethane urea solution will change, and no stratification will occur, showing the characteristics of direct dip coating processing.

[0066] 2) By Figure 1 The infrared spectra of the five samples show that -1 The characteristic absorption peak of isocyanate at 1705 cm -1 1541 cm -1New peaks also appear at 3300cm-1, which represent the carbonyl group in carbamate and CN in carbamate. -1 The infrared absorption peak of the NH bond at 1030 cm-1 gradually increases, indicating that the degree of hydrogen bonding in polyurethane urea also increases gradually. -1 The characteristic stretching vibration peak at is also clearly visible, which can confirm the successful preparation of polysiloxane polyether polyurethane urea.

[0067] 3) From Figure 2 As shown in Table 1, from the GPC test results, it can be seen that the number average molecular weights of the five samples synthesized by the present invention are all above 120,000, and the weight average molecular weights are all between 230,000 and 350,000. In particular, the number average molecular weights of Si40 and Si45 are both between 140,000 and 160,000, the weight average molecular weights are controlled in the range of 250,000 to 300,000, and the molecular weight distribution D is below 1.9, which is far higher than the molecular weight data of current commercial polyurethanes, and the molecular weight distribution is controlled to ensure the stability of product quality.

[0068] Table 1 Molecular weight and molecular weight distribution of polysiloxane polyether polyurethane urea with different hard segment contents

[0069] 4) For polymer materials used in polymer heart valves, the mechanical properties of the materials are crucial. Figure 3 (a) to Figure 3(c) and Table 2 are the evaluations of the tearing properties and tensile properties of the above materials in dry and wet environments. It can be seen that the tensile strength and elongation of the five materials are above 24MPa and 500% respectively; and with the continuous increase of the hard segment content, the elastic modulus and tear resistance of the polyurethane urea material also increase accordingly. The tensile strength of Si40 and Si45 both exceed 40MPa, exceeding the existing technology materials. In order to further simulate the in vivo use conditions, the materials were saturated with water and their mechanical properties were evaluated under wet conditions. The results show that the tensile strength and elongation at break of the above materials are above 20MPa and 500% respectively, far exceeding the 24MPa and 80% of the bovine pericardium cross-linked by glutaraldehyde. The tear strength of bovine pericardium is about 58N / mm, and the tear strength of polyurethane urea increases with the increase of the hard segment content under both dry and wet conditions. When the hard segment content reaches 36wt%, the tear strength of Si36 and Si40 is equivalent to that of bovine pericardium, indicating good tear resistance, while Si45 has been significantly improved. In addition, modulus is a key parameter to ensure leaflet movement, blood flow and overall valve sealing. For polymer materials used in heart valves, the tensile modulus should be less than 50MPa. The above materials can basically meet the requirements. The above materials have great prospects in the application of polymer heart valve materials.

[0070] 5) For implant / intervention materials, excellent biocompatibility is a crucial technical requirement. Taking the polymer material (Si40) synthesized in the present invention with a hard segment content of 40wt.% as an example, we conducted a biocompatibility test. Figure 4 They are cytotoxicity test and four coagulation tests. From the cytotoxicity test, it can be seen that compared with the positive control, the relative increase rate of Si40 is about 100%, and it has basically no toxic effect on cells. From the four coagulation tests, it can be seen that the results of the four coagulation tests are all within the normal range, and the material has no effect on the coagulation system. Combined with the cytotoxicity and four coagulation analyses, the material synthesized by the present invention shows excellent biocompatibility.

[0071] 6) In order to conduct a comprehensive analysis of the biostability of polymer materials, e.g. Figure 5As shown. The present invention conducts in vivo and in vitro degradation experiments on the synthesized polymer material (Si40) with a hard segment content of 40wt.%. The in vivo degradation experiment is to select 2-week-old rats weighing about 300g for the experiment. After the experimental rats are anesthetized, the sample pieces cut into a size of 1cm*1cm are implanted into the back of the rats. Four sample pieces are implanted into each rat, and each sample is repeated 8 times. After the material pieces are implanted for 30 days, the rats are killed by carbon dioxide and samples are taken. After the samples are taken, an electron microscope experiment is performed to observe the surface morphology of the material. The in vitro degradation experiment method is: soak the material to be tested in a mixed solution containing 1.63M hydrogen peroxide and 0.05M cobalt chloride, and oscillate and place it at 37 degrees Celsius for 30 days to simulate in vitro oxidation. After washing and drying, the SEM surface morphology is observed. The in vivo degradation experiment and the in vitro degradation experiment show that there is no obvious degradation on the surface of the material, showing excellent biological stability.

[0072] Table 2 Stress-strain test results of polysiloxane polyether polyurethane urea with different hard segment contents

[0073] The preparation is carried out by a bulk-solution polymerization method; first, at a relatively high temperature, a prepolymerization reaction is carried out in the form of a bulk using polyether diol, polydimethylsiloxane and diisocyanate; after the prepolymerization is completed, a secondary chain extender is added, and then the reaction is continued for a period of time at a set temperature, and then an appropriate amount of solvent is added to dissolve the reaction system into a solution, and the primary chain extender is added in the solution state and reacted at a suitable temperature for a period of time until the reaction is completed. This method is simple and reliable, and the prepared material has excellent biocompatibility, biostability, and mechanical properties. The prepared polyurethane urea material is a polymer heart valve material with great application prospects.

Claims

1. A polysiloxane polyether polyurethane urea, characterized in that: The polysiloxane polyether polyurethane urea consists of a hard segment and a soft segment; the hard segment content is 40wt.%~45wt.%, including diisocyanate and a small molecule chain extender; the soft segment includes polydimethylsiloxane and polyether, and the proportion of polydimethylsiloxane in the soft segment is 55-65%.

2. The polysiloxane polyether polyurethane urea according to claim 1, characterized in that The number average molecular weight of the polysiloxane polyether polyurethane urea is 140,000-160,000, the weight average molecular weight is 250,000-300,000, and the molecular weight distribution index is ≤1.

9.

3. The polysiloxane polyether polyurethane urea according to claim 1, characterized in that: The proportion of the polydimethylsiloxane in the soft segment is 60%.

4. The polysiloxane polyether polyurethane urea according to claim 1, characterized in that: The polyether is polytetrahydrofuran with a number average molecular weight of 500-3000; the polydimethylsiloxane is α,ω-bis(hydroxyethoxypropyl)polydimethylsiloxane with a number average molecular weight of 500-3000; and the diisocyanate is diphenylmethane diisocyanate.

5. The polysiloxane polyether polyurethane urea according to claim 4, characterized in that: The mass ratio of the diisocyanate to the hard segment is 70wt.%-75wt.%.

6. The polysiloxane polyether polyurethane urea according to claim 1, characterized in that: The small molecule chain extender includes a secondary chain extender and a primary chain extender, wherein the secondary chain extender is a C1-C6 diol, and the primary chain extender is a C1-C6 diamine.

7. The polysiloxane polyether polyurethane urea according to claim 6, characterized in that: The secondary chain extender is butanediol, and the primary chain extender is ethylenediamine.

8. The polysiloxane polyether polyurethane urea according to claim 7, characterized in that: The weight ratio of the butanediol to ethylenediamine is 3:

2.

9. The method for preparing the polysiloxane polyether polyurethane urea according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) polymerizing polyether diol and diisocyanate, wherein the molar ratio of the polyether diol to the diisocyanate is 2:1; (2) After the reaction in step (1) is completed, polydimethylsiloxane and diisocyanate are added into the system and heated for polymerization; (3) After the reaction in step (2) is completed, a secondary chain extender is added into the system for chain extension; (4) After the reaction in step (3) is completed, a main chain extender is added into the system for chain extension.

10. An artificial heart valve, wherein the material is the polysiloxane polyether polyurethane urea according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Polyurethane / urea compositions

    US20170119923A1

  • Polyurethane / urea materials

    CN114106278A

  • Polysiloxane-contg. polyurethane elastomeric compositions

    CN1299382A

  • Siloxane-containing polyurethane-urea compositions

    CN1352664A

  • Siloxane-containing polyurethane-urea compositions

    US20020028901A1